Dictionary of computer vision and image processing - Fisher, R. B. (John Wiley & Sons, 2014)
"The subjects of computer vision and image processing have advanced very much over the past 5 years, and keeping up to date in this fast-moving subject area can be very challenging.The Second Edition of the Dictionary of Computer Vision & Image Processing features over 3000 of the most commonly used terms in the field of computer vision, machine learning, image analysis and image processing, with approximately 1000 new terms having been identified for inclusion since the current edition was published. Revised to include an additional 1000 new terms to reflect current updates, which includes a significantly increased focus on image processing terms, as well as machine learning terms. Now includes citations to the terms to point to further reading about each term. Easy to follow structure with grouping of terms for ease of reference, comprehensive selection of terms, readers can use with confidence as written by leading researchers in the field. A new feature of this edition is the supplementary regrouping of related terms by concept. Illustrated throughout with associated diagrams and images provided to help clarify explanation. Fully revised and updated this Dictionary is ideal for Final year undergraduates, Masters and PhD students; and early stage career researchers in computer vision and image processing"--
Bibliografija:324-372 str.
Keywords: Computer vision -- Dictionaries; Image processing -- Dictionaries; COMPUTERS / Computer Vision & Pattern Recognition